Patients' body image after open abdominal surgery of abdominal aortic aneurysm - Perceptions and experiences - Monica Pettersson; Erney Mattsson; Ingegerd Bergbom (Wiley, 2022)
Abstract Aims To explore and gain an understanding of patients' perceptions and experiences of their body and bodily function in connection with open surgery of abdominal aortic aneurysm. Background After the operation of an abdominal aortic aneurysm (AAA) it may be difficult for the patients to understand what the procedure means. Design The design was descriptive and based on an analysis of 13 audio‐taped consultations with patients undergoing open surgery for AAA at a Swedish university hospital. The patients' age varied from 57-79 and the mean age was 71 (70.5 female). Methods A hermeneutic approach was used whereby patients were interviewed and draw a picture of their thoughts and experiences of the surgery and what had been done in their bodies. Once patients had finished their drawings, the interviewer asked what thoughts and experiences they had of the AAA. Results Patients described experiences as a process of "going from broken to whole again."